Renewable Energy Capacity Assessment in Power System Based on Linearized OPF - Yu DONG; Cun DONG; Ruoying YU; Jie DING (Zhongguo dianli)
With the deepening adjustment of energy structure, the penetration of renewable energy in power system is gradually increased. The fluctuation and randomness of renewable energy output have brought new challenges to the power system operation. It is of great significance for the planning and operation of power system with renewable energy to scientifically evaluate the capacity of renewable energy consumption. In this paper, a linear optimal power flow (OPF) model of renewable energy consumption capacity in power system was established. Considering the nonlinear characteristic of power system power flow, a linearization method was established to solve the problem that the traditional high-order nonconvex OPF model is difficult to obtain the global optimal solution. Considering the voltage magnitude, line power flow, power injection and the climbing constraints, the renewable energy consumption capacity of power system was evaluated. The effectiveness of the proposed OPF is verified by simulation analysis, and the main factors restricting renewable energy penetration are discussed with a standard testing system.